2008
DOI: 10.1128/aac.01230-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antibiotics on Quorum Sensing in Pseudomonas aeruginosa

Abstract: During infection, Pseudomonas aeruginosa employs bacterial communication (quorum sensing [QS]) to coordinate the expression of tissue-damaging factors. QS-controlled gene expression plays a pivotal role in the virulence of P. aeruginosa, and QS-deficient mutants cause less severe infections in animal infection models. Treatment of cystic fibrosis (CF) patients chronically infected with P. aeruginosa with the macrolide antibiotic azithromycin (AZM) has been demonstrated to improve the clinical outcome. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
266
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(289 citation statements)
references
References 97 publications
11
266
1
2
Order By: Relevance
“…Previous studies have provided evidence that antimicrobial agents at subinhibitory concentrations may induce alternations in bacterial properties, including changes in morphology and ultrastructure [53], as well as inhibition or stimulation of virulence factors [5456]. In our study, 1/4 MIC and 1/8 MIC of GH12 could slightly enhance acid production, and cause different changes in acid tolerance and EPS production (Figures 2–4).…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have provided evidence that antimicrobial agents at subinhibitory concentrations may induce alternations in bacterial properties, including changes in morphology and ultrastructure [53], as well as inhibition or stimulation of virulence factors [5456]. In our study, 1/4 MIC and 1/8 MIC of GH12 could slightly enhance acid production, and cause different changes in acid tolerance and EPS production (Figures 2–4).…”
Section: Discussionsupporting
confidence: 49%
“…These reductions coincided with reduced Las-and Rhl-dependent gene transcription and have been corroborated by microarray and proteomic studies (319,320), which found, in addition to QS gene misregulation, a reduction in levels of oxidative stress and motility-related genes but an increase in type III secretion (TTS)-related genes. The diminished response to oxidative stress conditions may account for the reduced cell viability in late stationary phase that was reported to occur with increasing concentrations of macrolides (318,319).…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 71%
“…In a screen of 11 antimicrobial compounds, a cephalosporin (ceftazidime [CFT]) and a fluoroquinolone (ciprofloxacin [CPR]) were also able to inhibit AHL production in P. aeruginosa and showed regulatory effects very similar to that seen for AZM, as determined by transcriptional profiling after treatment with each antibiotic (320). As the structural compositions of AZM, CFT, and CPR are highly divergent, it appears unlikely that each directly blocks activity of AHL synthase proteins and instead seems more probable that a separate, unifying theme for inhibition is at work.…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…If such QSIs are free of toxic side effects, they may be used to treat biofilm infections like chronic P. aeruginosa lung infections [71]. Interestingly, some antibiotics, like ceftazidime and ciprofloxacin and the macrolides azithromycin and clarithromycin [72], inhibit QS in P. aeruginosa at sub-MIC concentrations leading to inhibition of the virulence of these bacteria. However, azithromycin and clarithromycin, in contrast with ciprofloxacin and ceftazidime, cannot inhibit bacterial growth at obtainable concentrations in vivo.…”
Section: Quorum Sensing Inhibitors (Qsi)mentioning
confidence: 99%